Contemporary Development of Economic Sciences - Chobanova, Rossitsa (Research Papers, 2024)
The aim of the article is to contribute to a better understanding of the contemporary development of economic sciences, expressed in the emergence of new concepts for the development of the national economy. Among the concepts discussed are those of the knowledge economy, innovation economy, circular economy and digital economy. Their genesis and development is associated with the accelerated change of the technologies used and a corresponding change in economic relations. To determine these changes within individual concepts, data are used and toolkits developed by the OECD, Eurostat and the World Bank are applied.Based on the application of the little-known Hegelian understanding of the development of the economy and society, it is concluded that in their totality the new concepts characterize the transition to a new stage of economic development, which has a new goal, a subject and a toolbox of achievement. On this basis, as an important direction of future research in the field of economic sciences, the development of a nationally specific long-term strategy for the development of the national economy with an incorporation of modern concepts and an adequate national specifics prioritization of the goals, subjects and mechanisms of development is derived.